E-MONITORING INTERAKTIF MENINGKATKAN REFLEKSI DIRI, MOTIVASI BELAJAR DAN HASIL BELAJAR MAHASISWA DIII KEBIDANAN - Ratnasari, Eka; Permadi, Wiryawan; Hilmanto, Dany (Universitas Tribhuwana Tunggadewi, 2019)
The proportion of practice in Midwifery education has 60% of capacity, more than the proportion of theories which is only 40%. The biggest proportion of practice makes the Clinical Advisor and Academic Advisor try to provide immediate feedback to students in every skill learned in the practice field. Interactive, effective and corrective feedback can help students to do self-reflection so while in the practice field students expected to be motivated to improve learning outcomes. The purpose of this study was to define the effect of Interactive E-Monitoring implementation on self-reflection, motivation and learning outcomes of the student.A research population of this study is students of midwifery diploma program in thirdh semester of 2018/2019 Akademic year who take part in second Laboratory Learning Practices, which are spread over in 13 of independent midwife practice fields (PMB). Samples were taken in based on inclusion criteria, students who were guided by PK that included in the criteria and in aged 19-20 years were 56 students. Data analyzed, if the data is normally distributed then it uses paired t test and if the data is not normally distributed then it uses the Wilcoxon Test.The results showed that students self-reflection increased from 74.9 to 80.5 (p